2011
DOI: 10.1007/s10195-011-0143-1
|View full text |Cite
|
Sign up to set email alerts
|

Established non-union of an operatively managed trans-scaphoid perilunate fracture dislocation progressing to spontaneous union

Abstract: Perilunate dislocations and fracture dislocations represent uncommon and unusual injuries that are often missed at initial presentation and diagnosed late in up to 25% of cases. Prompt open reduction, carpal stabilisation and ligamentous repair is required to reduce the risk of complications. We report a case of an established scaphoid non-union in an operatively managed perilunate fracture dislocation that spontaneously united almost 2 years after the initial injury, just before a planned revision scaphoid fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Only limited case reports and case series of late spontaneous union of established pediatric scaphoid nonunion have been described. [5][6][7] However, these reports are isolated to waist and distal pole nonunions. Clarke et al and Manak et al have described cases of a 14-year-old and 11-yearold boys, both with a scaphoid waist nonunion that progressed to union at around 2 years following injury.…”
Section: Discussionmentioning
confidence: 95%
“…Only limited case reports and case series of late spontaneous union of established pediatric scaphoid nonunion have been described. [5][6][7] However, these reports are isolated to waist and distal pole nonunions. Clarke et al and Manak et al have described cases of a 14-year-old and 11-yearold boys, both with a scaphoid waist nonunion that progressed to union at around 2 years following injury.…”
Section: Discussionmentioning
confidence: 95%
“…As already mentioned, it is difficult to diagnose the scaphoid fractures with plain radiographs and different studies have cited the sensitivity of plain radiography after injury 59 to 79 percent which is relatively low ( 13 , 19 , 20 ). MRI is a gold standard for the diagnosis of this type of fracture, but its cost is relatively high ( 19 , 21 , 22 , 23 , 24 , 25 ). Therefore, it is felt the need for other ways with less cost and in order to eliminate additional costs, such as immobilization, referring to the clinic, delayed radiographic examinations, patients’ downtime after casting.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies identified nonunion of the scaphoid as the primary reason for reoperation. 11,12 It seems that, with current techniques and implants, scaphoid nonunion meriting additional surgery is uncommon. Among the factors associated with poor outcome in prior studies of PLDs (e.g., open injury, delayed treatment, osteochondral fracture of the capitate, and presence of persistent carpal malaligment), 1,21,22 only persistent carpal malalignment was associated with unplanned reoperation in the early recovery period.…”
Section: Discussionmentioning
confidence: 99%